Purification of polycarbonate from aluminum by acid leaching for recycling waste compact discs - Cui Li, Hui Wang (Science Faculty of Chiang Mai University, 2019)
Waste management receives increasing attention due to social and environmental pressures. This work deals with recycling waste compact discs (WCDs), and acid leaching was employed for purification of polycarbonate in WCDs from aluminum. The influence of temperature, concentration, leaching time, liquid–solid ratio, agitation and particle size on leaching of aluminum were investigated to optimize experimental parameters. Under the optimized conditions of temperature 50 °C, leaching time 5 h, liquid–solid ratio 10:1, acid concentration 2.5 mol L–1, agitation speed of 400 r min–1, and particle size 2–3mm, the leaching yield of aluminum was up to 86.72 %. The kinetic mechanism was examined to get a better understanding of leaching process. The leaching process was controlled by product layer diffusion model, and the activation energy was calculated to be 15.01 kJ mol–1. A reliable, environmentally friendly and cost–effective process was proposed for recycling WCDs, and economic analysis confirms economic feasibility of the process. This study provides technical insights into recycling of solid wastes